Flavour-changing neutral scalar interactions of the Top Quark - Castro, Nuno Filipe (2022)
A study of the top-quark interactions via flavour-changing neutral current (FCNC) processes provides an intriguing connection between the heaviest elementary particle of the standard model (SM) of particle physics and the new scalar bosons that are predicted in several notable SM extensions. The production cross sections of the processes with top-scalar FCNC interactions can be significantly enhanced to the observable level at the CERN Large Hadron Collider. The present review summarises the latest experimental results on the study of the top-quark interactions with the Higgs boson via an FCNC and describes several promising directions to look for new scalar particles.